Ceramic tile seam beautifying composition and ceramic tile seam beautifying method
By using 30 to 100 copies of light solid resin and 0.2 to 3 copies of light -induced tiles with light tiles, the existing tile filling material surface grooves, discoloration and dirty and dirty are used, and the construction is convenient, efficient, and efficient. The economic effect and improve the stability and mechanical strength of the materials.
Patent Information
- Application Number
- CN202411642105.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
AI Technical Summary
The existing ceramic tile caulking materials are prone to grooves on the surface after the joint is pressed, making it difficult to achieve flat joint construction, and it will change color and become dirty over time. There is a high cost of demolition and redoing and the risk of damaging the ceramic tile.
Provides a ceramic tile beautiful seam composition, including 30 to 100 parts of photocurable resin and 0.2 to 3 parts of photoinitiator. It can be cured and formed in a short time by simple illumination. It is suitable for various base layers and has excellent adhesion. Knot, flexibility and mechanical strength.
It achieves more convenient construction, higher efficiency and better economy. The cured and molded material has structural stability, chemical stability, sealing and mechanical strength, and avoids the problems of discoloration, contamination and damage of existing materials. .
Smart Images

Figure CN119350962A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic tile joint beautification composition and a ceramic tile joint beautification method, belonging to the field of ceramic tile joint beautification. Background Art
[0002] The commonly used tile caulking materials in home decoration are mainly epoxy resin, polyurea caulking agent and cement-based caulking agent. Among them, epoxy resin and polyurea caulking agent materials have gradually become the mainstream materials for tile caulking, but such materials are prone to grooves on the surface after pressing the seams, making it difficult to achieve flat seam construction. At the same time, such materials will also change color and become dirty over time. Removing such caulking materials and re-constructing them has the disadvantages of high costs and the risk of damaging tiles. Various types of cement-based caulking agents have a certain mildew-proof effect in the early stage, but they are still prone to mold and blackening in a humid and hot environment for a long time, affecting the overall appearance of the building, and there is a need for maintenance and upgrading. Furthermore, a large number of owners of fine-decorated houses who use cement-based caulking agents will choose to remove and redo epoxy or polyurea resin caulking agents after delivery, which will also cause a lot of labor and material waste.
[0003] Therefore, how to develop a caulking material that can be effectively integrated and bonded with conventional caulking materials such as cement, epoxy resin, polyurea resin, etc., and which is economical, convenient, and efficient when used for wall and floor leveling, repair, and color changing processes, and has good material stability, high sealing, and strong mechanical strength after construction is a problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the above technical problems, the object of the present invention is to provide a ceramic tile grouting composition and a ceramic tile grouting method, wherein the ceramic tile grouting composition can be cured and formed in a short time by simple light exposure.
[0005] To achieve the above object, the present invention provides a ceramic tile joint beautifying composition, which comprises 30 to 100 parts of a photocurable resin and 0.2 to 3 parts of a photoinitiator by weight. The photocurable resin is obtained by copolymerizing an acrylate monomer, an isocyanate-terminated polyurethane prepolymer and an epoxy resin prepolymer; the molar ratio of the isocyanate-terminated polyurethane prepolymer to the epoxy resin prepolymer is 1:0.5 to 1; the amount of the isocyanate-terminated polyurethane prepolymer and the acrylate monomer is measured according to a molar ratio of -NCO:-COO-CH=CH2 of 1:1 to 1.5.
[0006] The ceramic tile caulking composition of the present invention has excellent application effect when it is subsequently applied to wall and floor flat seams, maintenance, and color change processes. First, the ceramic tile caulking composition can adapt to various types of base materials including concrete, ceramic tiles, cement, epoxy resin, polyurea resin, etc., and has excellent adhesion to cement or concrete base, ceramic base, epoxy resin or polyurea resin base, and has good flexibility. Secondly, the ceramic tile caulking composition can be cured and formed in a short time by simple illumination, and the construction process is more convenient, more efficient, and more economical. Moreover, the cured material has excellent structural stability, chemical stability, sealing and mechanical strength. Furthermore, the present invention simultaneously adopts a light-transmitting filler in conjunction with the above-mentioned light-curing resin, which can allow more light to enter the deep layer of the gap in subsequent practical applications, thereby achieving the beneficial effect of efficient curing.
[0007] Furthermore, the acrylate monomer includes but is not limited to one or a combination of two or more of methyl acrylate, ethyl acrylate and butyl acrylate.
[0008] Further, the weight average molecular weight of the terminal isocyanate polyurethane prepolymer is 300 to 1500. In an optional embodiment, the above-mentioned terminal isocyanate polyurethane prepolymer can be directly commercially available, or it can be obtained by copolymerization of isocyanate and diol. Among them, the diol can be selected from ether diols and / or ester diols, such as polyether diols, polyether triols, polyoxypropylene diols, and polyoxypropylene triols. Isocyanates are preferably saturated isocyanates, such as hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate. Such isocyanates can further provide good yellowing resistance for tile seam materials.
[0009] Specifically, the isocyanate-terminated polyurethane prepolymer can be obtained by polymerization of isocyanate and diol under catalyst conditions according to the molar ratio of -NCO:-OH of 1:0.5 to 1. The catalyst can be selected from one or a combination of two or more of tin catalysts (such as dibutyltin dilaurate (T12)), amine catalysts (such as 1,8-diazobisspiro[5.4.0]undec-7-ene (DBU)), titanium catalysts and bismuth catalysts.
[0010] Furthermore, the weight average molecular weight of the epoxy resin prepolymer is 650 to 4000, and it is a solid epoxy resin. The epoxy resin prepolymer can be directly purchased from the market, or it can be prepared by itself. For example, in an optional embodiment, bisphenol A epoxy resin and amine can be mixed and reacted in a molar ratio of 10:0.5 to 2. Among them, the amine can be selected from one or a combination of two or more of 1,3-cyclohexanedimethylamine, isophorone diamine and polyether amine.
[0011] Specifically, in an optional embodiment, the photocurable resin can be prepared by the following steps:
[0012] First, add isocyanate, diol and catalyst into the reactor in a molar ratio of -NCO: -OH of 1:0.5-1, stir and react. The reaction temperature is initially set to 40°C. Because the polyurethane reaction is an exothermic reaction, it is easy to explode if the temperature is too high at the beginning. The reaction temperature can be set to 60-80°C in the later stage to allow the reactive groups to react fully to obtain an isocyanate-terminated polyurethane prepolymer.
[0013] Secondly, maintaining the temperature at 60-80° C., epoxy resin prepolymer is further added to the above reaction system at a molar ratio of 1:0.5-1 of terminal isocyanate polyurethane prepolymer:epoxy resin prepolymer to form oxazolidinone ring segments.
[0014] Next, maintaining the temperature at 60-80° C., add acrylate monomer to the above reaction system at a molar ratio of -NCO:-COO-CH=CH2 of 1:1-1.5 to continue the reaction, thereby obtaining the above photocurable resin.
[0015] In a preferred embodiment, the ceramic tile grouting composition further comprises 40 to 60 parts of a light-transmitting filler, 0.5 to 5 parts of a thickener, 0.2 to 10 parts of a diluent, and 0.2 to 5 parts of a UV pigment. The ceramic tile grouting composition is a paste-like liquid, and the material obtained therefrom has a suitable consistency and leveling property. Subsequently, by simple coating, filling, and curing, the application requirements of grouting, maintenance, and color change can be achieved.
[0016] Furthermore, the UV pigment is selected from inorganic color powder and / or organic color paste. The types of inorganic color powder and organic color paste are not particularly limited. Those skilled in the art can use UV pigments in the field of tile grouting, which will not be elaborated here. It should be noted that when the UV pigment is selected from light colors (such as light gray, light yellow, light brown, white, etc.), or the composition does not contain UV pigments, translucent fillers do not need to be added, and when the UV pigment is selected from dark colors (such as dark gray, dark brown, black, etc.), translucent fillers need to be added to the composition to improve the curing effect of the material.
[0017] In a preferred embodiment, the tile grouting composition includes, by weight, 30 to 100 parts of a photocurable resin, 0.5 to 1 part of a photoinitiator, 40 to 60 parts of a light-transmitting filler, 0.2 to 1 part of a diluent, 0.5 to 3 parts of a thickener, and 0.2 to 3 parts of a UV pigment.
[0018] In a preferred embodiment, the light-transmitting filler is selected from one or more of glass (e.g., solid glass microspheres, hollow glass microspheres, glass powder) and transparent resin (e.g., PP and / or PE transparent resin particles). Further, the particle size of the light-transmitting filler is 1 to 200 μm, for example, 1 μm, 10 μm, 50 μm, 100 μm, 150 μm or 200 μm.
[0019] In a preferred embodiment, the photoinitiator is selected from one or a combination of two or more of benzoin and its derivatives, benzil, alkylphenone, acylphosphine oxide, benzophenone, thioxanthone, iodonium salt and ferrocenium salt.
[0020] Further, benzoin and its derivatives photoinitiators include but are not limited to one or a combination of two or more of benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether and benzoin butyl ether. Benzyl photoinitiators include but are not limited to diphenylacetophenone and / or α,α-dimethoxy-α-phenylacetophenone. Alkyl phenone photoinitiators include but are not limited to one or a combination of two or more of α,α-diethoxyacetophenone, α-hydroxyalkyl phenone and α-aminoalkyl phenone. Acylphosphine oxide photoinitiators include but are not limited to aromatic acylphosphine oxide and / or bisbenzoylphenylphosphine oxide. Benzophenone photoinitiators include but are not limited to benzophenone and / or 2,4-dihydroxybenzophenone, Michler's ketone. Thioxanthone photoinitiators include but are not limited to thiopropoxythioxanthone and / or isopropylthioxanthone. Ionium salt photoinitiators include, but are not limited to, one or a combination of two or more of diaryl iodonium salts, triaryl iodonium salts, and alkyl iodonium salts. Aromatic ferrocenium salt photoinitiators include, but are not limited to, cumene ferrocenium hexafluorophosphate.
[0021] Further, the thickener is selected from one or a combination of two or more of fumed silica (hydrophilic fumed silica and / or hydrophobic fumed silica), bentonite, polyurethane thickener (e.g. 12W, 8W, U905) and acrylic thickener (e.g. ASE60, EXP60, DR50). The diluent is selected from ether diluent (e.g. ethylene glycol butyl ether, ethylene glycol ethyl ether) and / or polyether glycerol ester diluent (e.g. glycerol polyoxyethylene ether).
[0022] In a preferred embodiment, the above-mentioned ceramic tile grouting composition can be prepared by the following steps: prepare the raw materials according to the material formula, first add the photocurable resin into the mixing tank, turn on the disperser of the mixing tank, maintain the rotation speed at 100-300 rpm, then add the diluent and UV pigment into the mixing tank in turn and disperse them evenly, then slowly add the thickener until the thickener is completely integrated into the system, then add the translucent filler, and continue to stir for 8-15 minutes while vacuuming to obtain the ceramic tile grouting composition.
[0023] The present invention also provides a method for beautifying the joints of ceramic tiles, which comprises: placing the aforementioned ceramic tile joint beautifying composition at the location where the joints of the ceramic tiles are to be beautified and performing a light curing treatment.
[0024] Furthermore, the wavelength of light during the photocuring process is 250-800 nm, and the power is 5-2000 W.
[0025] In a preferred embodiment, the method for beautifying the joints of tiles comprises the following steps: step S1, pasting masking tape along the edge of the tile where the joints are to be beautified; step S2, placing the tile joint beautifying composition at the tile where the joints are to be beautified and flattening it with a joint pressing sheet, and then tearing off the masking tape; step S3, using a lighting device to perform a photocuring treatment on the tile where the joints are to be beautified (preferably 1 to 10 cm away from the tile where the joints are to be beautified) to complete the tile joint beautification. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 shows an infrared spectrum of the photocurable resin in an embodiment of the present invention;
[0027] Figure 2 A photograph showing the morphology of the ceramic tile joint beautifying composition after curing in Comparative Example 2 of the present invention is shown;
[0028] Figure 3 The morphology photograph of the tile joint beautifying composition after curing in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0029] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0030] The ceramic tile caulking composition in the embodiment and the comparative example is prepared by the following steps: prepare raw materials according to the material formula (by weight, the raw material formula of the embodiment and the comparative example is shown in Table 1), first add the photocurable resin into the mixing tank, turn on the disperser of the mixing tank, keep the speed at 200 rpm, then add the diluent and UV pigment into the mixing tank in turn and disperse them evenly, then slowly add the thickener until the thickener is completely integrated into the system, then add the translucent filler, and continue to stir for 10 minutes while vacuuming to obtain the ceramic tile caulking composition.
[0031] Table 1
[0032]
[0033] Note: The sources of the raw materials in Table 1 are as follows:
[0034] (1) The photocurable resin is prepared by the following steps: hexamethylene diisocyanate and diol are added into the reactor at a molar ratio of -NCO:-OH of 1:0.6. The reaction is stirred under the action of an organic tin catalyst. The initial reaction temperature is set to 40°C, and the later reaction temperature is set to 60-80°C. The reaction is fully reacted for 3 hours to obtain a terminal isocyanate polyurethane prepolymer.
[0035] The temperature is maintained at 60-80° C., and epoxy resin prepolymer is added to the system at a molar ratio of isocyanate-terminated polyurethane prepolymer to epoxy resin prepolymer of 1:0.5. The isocyanate reacts with the epoxy resin prepolymer to form an oxazolidinone ring segment.
[0036] The reaction temperature was maintained at 60-80°C, and acrylate monomer was added at a molar ratio of -NCO:-COO-CH=CH2 of 1:1. The reaction was continued for 2 hours. After the reaction was completed, a light-curable resin was obtained, and the structural formula was:
[0037]
[0038] In the formula,
[0039] R1 is -(CH2)2-CONH-;
[0040] R2 is
[0041] R3 is -(CH2)4-;
[0042] R4 is
[0043] n is 3.
[0044] Infrared spectrum of photocurable resin Figure 1 shown.
[0045] (2) Solid glass microspheres: particle size is 38-74 μm.
[0046] (3) Hollow glass microspheres: particle size is 38 to 150 μm.
[0047] (4) Glass powder: particle size is 3 to 30 μm.
[0048] (5) Transparent resin particles: a mixture of PP and PE resin particles with a particle size of 74 to 300 μm.
[0049] (6) Photoinitiator: benzophenone.
[0050] (7) Diluent: glycerol polyoxyethylene ether.
[0051] (8) Thickener: hydrophobic fumed silica.
[0052] (9) UV pigment: Examples 1 to 4 and 7 to 15 all use dark grey UV pigment, Example 5 uses light grey UV pigment, and Example 6 uses light brown UV pigment.
[0053] Performance characterization:
[0054] (i) The tile joint beautifying compositions prepared in the above embodiments and comparative examples were sampled on the tile surface specified in 7.11.2.1 of JC / T547-2017, the brick surface after being coated with epoxy resin joint beautifying agent, the brick surface after being coated with polyurea joint beautifying agent, and the cement mortar block specified in GB / T17671-1999. When preparing the sample, each tile joint beautifying composition in the embodiments and comparative examples of the present invention was coated (coating thickness was 0.5 mm) on the base to be tested, and irradiated with a matching lamp (light wavelength of 365 nm, power of 50 w) for 10 s, and then the adhesion test was carried out according to the method specified in GB / T5210-2006. The test results are shown in Table 2.
[0055] Table 2
[0056]
[0057] As can be seen from Table 2, the ceramic tile joint beautifying composition of the embodiment of the present invention can adapt to various base layers including concrete, ceramic tile, cement, epoxy resin, polyurea and other types of materials, and has excellent bonding performance. Among them, the bonding performance is better for epoxy resin, because the photocurable resin of the present invention contains epoxy resin, which can combine with the unreacted amine in the base layer to form a strong bond on the epoxy resin base layer. Comparative Example 1 reduces the addition ratio of the photocurable resin and increases the addition ratio of the filler, and the bonding strength of the material on various base layers is reduced.
[0058] Preferably, it can be further illustrated by Example 1, Example 8 and Example 9 that when the amount of photoinitiator is preferably 0.5 to 1 part (for example, Example 1 and Example 9), the material strength performance is excellent. When the amount of photoinitiator is lower than this range (for example, Example 8), the degree of material curing is slightly low and the material strength is slightly low. When the amount of photoinitiator is higher than this range, continuing to increase the amount of photoinitiator will no longer significantly increase the material strength and result in a large loss of raw materials.
[0059] Preferably, it can be further illustrated by Example 1, Example 10, and Example 11 that when the amount of diluent is preferably 0.2 to 1 part (such as Example 1 and Example 10), the material bonding strength performance is excellent. When the amount of diluent is higher than this range (such as Example 11), the material is thinner, resulting in reduced strength. When the amount of diluent is lower than this range, the material has a high consistency and the subsequent coating performance is slightly poor.
[0060] Preferably, it can be further illustrated by Example 1, Example 12, and Example 13 that when the amount of thickener is preferably 0.5 to 3 parts (such as Example 1 and Example 12), the material bonding strength performance is excellent. The thickener itself is a filler. When the amount of thickener is higher than this range (such as Example 13), the proportion of opaque filler in the formula will increase, affecting light transmittance, the degree of material curing will be affected, and the material bonding strength will be reduced. When the amount of thickener is lower than this range, the material is highly diluted and the subsequent coating performance is slightly poor.
[0061] Preferably, it can be further illustrated by Example 1, Example 14, and Example 15 that when the amount of UV pigment is preferably 0.2 to 3 parts (such as Example 1 and Example 14), the comprehensive bonding performance of the material is excellent. When the amount of UV pigment is higher than this range (such as Example 15), the curing of the material will be affected and the bonding strength of the material will be reduced. When the amount of UV pigment is lower than this range, the color of the material will decrease.
[0062] (II) Taking Example 1 as an example, a 50W ultraviolet lamp (250-350nm) was fixed, and the bonding strength test results of the tile joint beautifying composition of Example 1 on the epoxy resin joint beautifying agent base layer under different irradiation times are shown in Table 3.
[0063] Table 3
[0064]
[0065] As can be seen from Table 3, the ceramic tile caulking composition of the present invention can be cured and formed in a short time by simple light irradiation, and the construction process is more convenient, more efficient and more economical. Furthermore, under the condition of fixed wattage and light wavelength, the longer the irradiation time, the greater the degree of curing and the higher the bonding strength, but after a certain time, the material is completely cured and the bonding strength no longer increases, which wastes energy.
[0066] Comparative Example 2
[0067] The only difference from Example 1 is that the photocurable resin is AgiSyn1030.
[0068] like Figure 2As shown in the figure, the UV resin in Comparative Example 2 is too rigid, and the tile joint beautifying composition will crack seriously during the curing process; the adhesion is insufficient, and the tile joint beautifying composition will debond with various bases (cement or concrete base, ceramic, epoxy resin or polyurea). However, the tile joint beautifying composition in Example 1 does not have any cracking problem after curing. Figure 3 shown.
Claims
1. A ceramic tile seam beautifying composition, wherein: The tile joint beautifying composition comprises 30 to 100 parts of a photocurable resin and 0.2 to 3 parts of a photoinitiator in parts by weight; The photocurable resin is obtained by copolymerizing an acrylate monomer, an isocyanate-terminated polyurethane prepolymer and an epoxy resin prepolymer; the molar ratio of the isocyanate-terminated polyurethane prepolymer to the epoxy resin prepolymer is 1:0.5-1; the amounts of the isocyanate-terminated polyurethane prepolymer and the acrylate monomer are measured according to a molar ratio of -NCO:-COO-CH=CH2 of 1:1-1.
5.
2. The tile joint beautifying composition according to claim 1, wherein: The tile grouting composition further comprises, by weight, 40 to 60 parts of a light-transmitting filler, 0.2 to 10 parts of a diluent, 0.5 to 5 parts of a thickener, and 0.2 to 5 parts of a UV pigment.
3. The ceramic tile joint beautifying composition according to claim 2, wherein: The tile grouting composition comprises, by weight, 30 to 100 parts of a photocurable resin, 0.5 to 1 part of a photoinitiator, 40 to 60 parts of a light-transmitting filler, 0.2 to 1 part of a diluent, 0.5 to 3 parts of a thickener, and 0.2 to 3 parts of a UV pigment.
4. The tile joint beautifying composition according to claim 2, wherein: The light-transmitting filler is selected from glass and / or transparent resin.
5. The tile joint beautifying composition according to claim 4, wherein: The particle size of the translucent filler is 1 to 200 μm.
6. The tile joint beautifying composition according to claim 1, wherein: The photoinitiator is selected from one or a combination of two or more of benzoin and its derivative photoinitiators, benzyl photoinitiators, alkyl phenone photoinitiators, acylphosphine oxide photoinitiators, benzophenone photoinitiators, thioxanthone photoinitiators, iodonium salt photoinitiators and ferrocenium salt photoinitiators.
7. The tile joint beautifying composition according to claim 2, wherein: The UV pigment is selected from inorganic color powder and / or organic color paste.
8. The tile joint beautifying composition according to claim 2, wherein: The thickener is selected from one or a combination of two or more of fumed silica, bentonite, polyurethane thickener and acrylic thickener; the diluent is selected from ether diluent and / or polyether glycerol ester diluent.
9. A method for beautifying the joints of ceramic tiles, wherein: include: The ceramic tile joint beautifying composition according to any one of claims 1 to 8 is placed at the ceramic tile joint to be beautified and subjected to light curing treatment.
10. The method for beautifying the joints of ceramic tiles according to claim 9, wherein: The wavelength of light in the photocuring process is 250-800nm, and the power is 5-2000w.
Citation Information
Patent Citations
Method for preparing resin for UV photocuring ink
CN101698698A
Ceramic-based interlaminar composite material formed based on photocuring and preparation method thereof
CN107032797A
Epoxy-modified urethane acrylate aqueous dispersion and preparation method thereof
CN108976381A
Joint sealant, tool for processing joint sealant, kit and illuminating means
CN110291121A
Epoxy resin prepolymer with split-phase structure as well as preparation method and application thereof
CN111004472A